Psychological Impact and Coping Strategies of Frontline Medical Staff in Hunan Between January and March 2020 During the Outbreak of Coronavirus Disease 2019 (COVID‑19) in Hubei, China - Cai, Haozheng; Tu, Baoren; Ma, Jing; Chen, Limin; Fu, Lei; Jiang, Yongfang; Zhuang, Quan (Medical science monitor, 2020)
BACKGROUND Throughout China, during the recent epidemic in Hubei province, frontline medical staff have been responsible for tracing contacts of patients infected with coronavirus disease 2019 (COVID‑19). This study aimed to investigate the psychological impact and coping strategies of frontline medical staff in Hunan province, adjacent to Hubei province, during the COVID‑19 outbreak between January and March 2020. MATERIAL AND METHODS A cross-sectional observational study included doctors, nurses, and other hospital staff throughout Hunan province between January and March 2020. The study questionnaire included five sections and 67 questions (scores, 0-3). The chi-squared χ² test was used to compare the responses between professional groups, age-groups, and gender. RESULTS Study questionnaires were completed by 534 frontline medical staff. The responses showed that they believed they had a social and professional obligation to continue working long hours. Medical staff were anxious regarding their safety and the safety of their families and reported psychological effects from reports of mortality from COVID‑19 infection. The availability of strict infection control guidelines, specialized equipment, recognition of their efforts by hospital management and the government, and reduction in reported cases of COVID‑19 provided psychological benefit. CONCLUSIONS The COVID‑19 outbreak in Hubei resulted in increased stress for medical staff in adjacent Hunan province. Continued acknowledgment of the medical staff by hospital management and the government, provision of infection control guidelines, specialized equipment and facilities for the management of COVID‑19 infection should be recognized as factors that may encourage medical staff to work during future epidemics.